Inoculation method with sclerotia of Agroathelia rolfsii (Sacc.) Redhead & Mullineaux in soybean (Glycine max L. Merr.) crops - Ibáñez-Marín, Yanina (2025)
Introduction. Agroathelia rolfsii (Sacc.) Redhead & Mullineaux is a polyphagous soil pathogen capable of affecting a variety of species, including the soybean crop. Its incidence can cause a decrease in the number of plants and yield losses ranging from 10-25% in normal years to over 50% in severe outbreaks, depending on the areas affected. Objective. To determine the minimum dose of sclerotia that causes symptoms in soybean plants. Materials and methods. Bioassays were carried out in a growth chamber. Three different doses of sclerotia 0.163 g, 0.326 g and 0.489 g per experimental unit were applied. Results and discussion. Significant differences in disease severity were found among treatments. Treatments with 0.326 g and 0.489 g of sclerotia expressed 70 and 82% symptoms, respectively. Necrosis at the base of the stem and the presence of cankers were the predominant symptoms. The pathogen dose used established a linear relationship between symptom occurrence and sclerotia dose, described by the equation: % PCS = 7.00 + 170.16 * D (g). A significant negative correlation of -0.40 (p = 0.0144) was observed between stem fresh weight and dose of the pathogen. Conclusion. The results obtained indicate that the minimum inoculum dose of 0.163 g of sclerotia can induce disease expression in the soybean crop.